2014
DOI: 10.1021/es404866z
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Experiment on Physiological Responses to Synergetic Effects of Ocean Acidification and Photoperiod in the Antarctic Sea Ice Algae Chlamydomonas sp. ICE-L

Abstract: Studies on ocean acidification have mostly been based on short-term experiments of low latitude with few investigations of the long-term influence on sea ice communities. Here, the combined effects of ocean acidification and photoperiod on the physiological response of the Antarctic sea ice microalgae Chlamydomonas sp. ICE-L were examined. There was a general increase in growth, PSII photosynthetic parameters, and N and P uptake in continuous light, compared to those exposed to regular dark and light cycles. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Photoperiod controls the total light dose received by phytoplankton and thus could remarkably influence the physiological performance such as growth and lipid content of microalgae (Wahidin et al, 2013). For Antarctic sea ice microalgae Chlamydomonas sp., continuous illumination stimulates higher growth and nutrient absorption rates than successive darkness condition (Xu et al, 2014c).…”
mentioning
confidence: 94%
“…Photoperiod controls the total light dose received by phytoplankton and thus could remarkably influence the physiological performance such as growth and lipid content of microalgae (Wahidin et al, 2013). For Antarctic sea ice microalgae Chlamydomonas sp., continuous illumination stimulates higher growth and nutrient absorption rates than successive darkness condition (Xu et al, 2014c).…”
mentioning
confidence: 94%
“…Some have just examined the effects of increased CO 2 concentration in isolation (Coad et al, 2016;Torstensson et al, 2015), while others have looked at the combined effects of costressors such as temperature (Pančić et al, 2015;Torstensson, 2012a, b), light (Xu et al, 2014a;Heiden et al, 2016) or iron (Xu et al, 2014b). Most studies have been undertaken on cultures of single species in a laboratory (Mitchell and Beardall, 1996;Xu et al, 2014a;Pančić et al, 2015;Torstensson et al, 2012a, b;Young et al, 2015), although there has been one study of a brine community (Coad et al, 2016) and two in situ experiments on brine communities . All but one of these studies (Torstensson et al, 2015) was conducted on a timescale of less than 30 days and most were less than 10 days (Table 1).…”
Section: Sea Ice Algaementioning
confidence: 99%
“…These authors also showed that there were large variations in species-specific responses. The growth and photosynthetic response of the chlorophyte Chlamydomonas, isolated from Antarctic sea ice, to ocean acidification and photoperiod, was examined by Xu et al (2014a) over the course of 28 days. While Chlamydomonas is not a common ice algal taxon, it nonetheless represents an organism adapted to living in the ice.…”
Section: Sea Ice Algaementioning
confidence: 99%
“…Changes in seawater carbon chemistry may also have varying effects on diatoms, as found in both short-and longterm studies (e.g., Tatters et al, 2013;Xu et al, 2014). These silicifiers (diatoms) form large blooms, account for a major fraction of primary production (Rost et al, 2003), and are of particular interest because they strongly influence the vertical flux of particulate material (Buesseler, 1998).…”
Section: Remote Sensing Of Biological Processes Relevant To Oamentioning
confidence: 99%